The Impact of Electric Online Taxi Innovation on Non-Electric Online Taxi Drivers in Indonesia - Destia Restu Ramanda (International Journal of Economics, Science, and Education, 2026)
This study aims to examine the direct and indirect effects of electric online taxi service innovation on non-electric online taxi drivers in Indonesia. A survey was conducted on 100 non-electric online taxi drivers. Sampling was carried out using a non-random sampling technique with a purposive sampling method. The research instrument was a questionnaire with a Likert scale of 1-4. The data analysis technique used Structural Equation Modeling with the Smart PLS application. It can be seen from the results of the analysis above that the environmentally friendly factor (ECO) does not significantly affect the competition (COM) between electric and non-electric online taxis (H2). Then, the existence (EXT) of electric taxis also does not directly affect the impact (IMP) caused to non-electric online taxi drivers (H4). Meanwhile, the existence (EXT) of electric online taxis has an indirect effect or through mediation of competition (COM) on (IMP) the impact on non-electric online taxi drivers (H6). Thus, the existence (EXT) of online electric taxis have a direct impact (IMP) on non-electric taxi drivers in terms of competition (COM) (H1) and (H3). Finally, the environmentally friendly factor (ECO) has a significant direct impact (H5) and without mediation variable Competition (COM) (H7). In conclusion, the innovation of electric online taxi is make direct and indirect effects on non-electric online taxi drivers in Indonesia.